2016
DOI: 10.1117/1.nph.4.3.031203
|View full text |Cite
|
Sign up to set email alerts
|

Parallel pathways from whisker and visual sensory cortices to distinct frontal regions of mouse neocortex

Abstract: Abstract. The spatial organization of mouse frontal cortex is poorly understood. Here, we used voltage-sensitive dye to image electrical activity in the dorsal cortex of awake head-restrained mice. Whisker-deflection evoked the earliest sensory response in a localized region of primary somatosensory cortex and visual stimulation evoked the earliest responses in a localized region of primary visual cortex. Over the next milliseconds, the initial sensory response spread within the respective primary sensory cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
5
17
0
Order By: Relevance
“…The database supports that the MO s and the V RL/A/AL are strongly linked with each other. In addition, the database confirms the parallel reciprocal pathways reported in the frontal-parieto-occipital cortex 44 , 45 ; the secondary motor area ~0.5 mm rostrolateral to our injection site is reciprocally linked with the primary somatosensory cortex (Supplementary Fig. 12e, l ), and the dorsal part of the anterior cingulate area is linked with the V1 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 84%
“…The database supports that the MO s and the V RL/A/AL are strongly linked with each other. In addition, the database confirms the parallel reciprocal pathways reported in the frontal-parieto-occipital cortex 44 , 45 ; the secondary motor area ~0.5 mm rostrolateral to our injection site is reciprocally linked with the primary somatosensory cortex (Supplementary Fig. 12e, l ), and the dorsal part of the anterior cingulate area is linked with the V1 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 84%
“…We did see a fast increase in local field potential amplitude (latency of approximately 50 ms, data not shown) after the first touch for each trial, but we cannot exclude the possibility that this local field potential carries multimodal information. When the mPFC does not encode sensory information directly, the alternative explanation could be that sensory information from primary sensory cortices is summarized by feature extraction and/or categorization (Hanks et al, 2015 ) in an upstream brain region, e.g., the more dorsal parts of frontal cortex (Sreenivasan et al, 2017 ) or the orbitofrontal cortex as has been suggested by Euston et al ( 2012 ), since there is strong innervation from both these regions to mPFC (Hoover and Vertes, 2007 ). During our task we do not identify specific sensory spiking patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Grasps varied in terms of different patterns of digit contact with the pasta (Fig. 9 ) but had two functions, to support the pasta and direct it into the mouth and to guide or hold the pasta in the mouth 22 . Guide grasps .…”
Section: Methodsmentioning
confidence: 99%